Harvesting space for a Greener Earth - Matloff, Greg (Springer New York, 2014)
What was our planet like in years past? How has our civilization affected Earth and its ecology? Harvesting Space for a Greener Planet, the Second Edition of Paradise Regained: The Regreening of the Earth, begins by discussing these questions, and then generates a scenario for the restoration of Earth. It introduces new and innovative ideas on how we could use the Solar System and its resources for terrestrial benefit. The environmental challenges that face us today cannot be resolved by conservation and current technologies alone. Harvesting Space highlights the risk of humankind's future extinction from environmental degradation. Population growth, global climate change, and maintaining sustainability of habitats for wildlife are all considered, among other issues. Rather than losing heart, we need to realize that the solutions to these problems lie in being good stewards of the planet and in the development of space. Not only will the solutions offered here avert a crisis, they will also provide the basis for continued technological and societal progress. Tapping the resources of near-Earth asteroids will lead to methods of diverting those asteroids that threaten Earth. Space-based terrestrial power generation systems will work synergistically with Earth-based conservation. This book needs to be read urgently and widely, if we are to save ourselves from environmental disaster, reduce the risk of catastrophic cosmic impacts, and build a prosperous and sustainable future for all the creatures of Earth.